Hierarchical Integration of Organic Core/Shell Microwires for Advanced Photonics - Lin, Hong‐Tao; Ma, Ying‐Xin; Chen, Song; Wang, Xue‐Dong (Angewandte Chemie International Edition, 2023)
The combination of multiple components or structures into integrated micro/nanostructures for practical application has been pursued for many years. Herein, a series of hierarchical organic microwires with branch, core/shell (C/S), and branch C/S structures are successfully constructed based on organic charge transfer (CT) cocrystals with structural similarity and physicochemical tunability. By regulating the intermolecular CT interaction, single microwires and branch microstructures can be integrated into the C/S and branch C/S structures, respectively. Significantly, the integrated branch C/S microwires, with multicolor waveguide behavior and branch structure multichannel waveguide output characteristics, can function as an optical logic gate with multiple encoding features. This work provides useful insights for creating completely new types of organic microstructures for integrated optoelectronics. Using a series of organic charge transfer cocrystals with structural similarity and physicochemical tunability, we demonstrate the precise construction of various types of hierarchical organic microwires. Branch microwires with multichannel waveguide and core/shell microwires with multicolor waveguide performance can be integrated into branch core/shell microwires for realizing optical logic gates with multi‐encoding functions.